2004
DOI: 10.1111/j.1462-2920.2004.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcolonies, quorum sensing and cytotoxicity determine the survival of Pseudomonas aeruginosa biofilms exposed to protozoan grazing

Abstract: This study was based on the hypothesis that biofilms of the opportunistic pathogen Pseudomonas aeruginosa are successfully adapted to situations of protozoan grazing. We tested P. aeruginosa wild type and strains that were genetically altered, in structural and regulatory features of biofilm development, in response to the common surface-feeding flagellate Rhynchomonas nasuta. Early biofilms of the wild type showed the formation of grazing resistant microcolonies in the presence of the flagellate, whereas biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
209
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(227 citation statements)
references
References 44 publications
7
209
2
2
Order By: Relevance
“…Inducible defences have been found in widely different organisms from prokaryotes (Patterson & Bolis, 1997;Matz et al, 2004) to diatoms (Lu¨rling & Van Donk, 2000), ciliates (e.g. Hammill et al, 2009) and various green, red and brown macroalgae (Toth & Pavia, 2007), but investigations into the transcriptomic changes associated with induced chemical defences have largely been restricted to angiosperm model organisms (Arimura et al, 2000;Reymond et al, 2004;De Vos et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Inducible defences have been found in widely different organisms from prokaryotes (Patterson & Bolis, 1997;Matz et al, 2004) to diatoms (Lu¨rling & Van Donk, 2000), ciliates (e.g. Hammill et al, 2009) and various green, red and brown macroalgae (Toth & Pavia, 2007), but investigations into the transcriptomic changes associated with induced chemical defences have largely been restricted to angiosperm model organisms (Arimura et al, 2000;Reymond et al, 2004;De Vos et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, all bacterial selection lines (eight clones from each) were grown individually with every predator species they had been exposed to during the selection experiment. Briefly, all protist measurement plates were inoculated with 20 μl of ancestral stock protist (approximately 100 cells ml − 1 ), and after 48 h of co-cultivation at 22°C, bacterial defence was determined as the amount of bacterial biofilm biomass; previous studies have shown that bacteria use biofilm aggregation as a size-dependent defence mechanism against protist predators (Matz et al, 2004;Friman and Laakso, 2011;. Bacterial biofilm growth was measured by adding 50 μl of 1% crystal violet solution to microplate wells and rinsed off with distilled water after 10 min.…”
Section: Measuring Bacterial Defence Against Protistsmentioning
confidence: 99%
“…This is in contrast to their planktonic single species population counterparts commonly studied in laboratory conditions. The formation and dispersal of structured bacterial biofilms or aggregates occur in response to a range of environmental cues and signals, such as changes in nutrient concentrations, oxygen, temperature, as well as chemicals and predatory stresses (Bassler et al, 1993;Matz et al, 2004;McDougald et al, 2011;Mitri et al, 2011). In many cases, the signal transduction pathways, the associated changes in gene expression and the involvement of second messenger systems have also begun to be unravelled (Barraud et al, 2009;Petrova and Sauer, 2012).…”
Section: Introductionmentioning
confidence: 99%